Prevalence and prognosis of acute ischemic stroke coexisting with unruptured intracranial aneurysms - Yan, Yujia; An, Xingwei; Ren, Hecheng; Luo, Bin; Han, Jin; Jin, Song; Liu, Li; Huang, Ying (Frontiers in Neurology, 2023)
Objectives The prevalence of unruptured intracranial aneurysms (UIAs) in the acute ischemic stroke (AIS) cohort is probably higher than in the general population. This study investigated the prevalence of UIAs in AIS patients and the management risk and prognosis when treating AIS. Methods From January 2020 to January 2023, we conducted a single-center retrospective study at Tianjin Huanhu Hospital. Each patient underwent both brain MRI and MRA/CTA to diagnose AIS and UIAs. Clinical, radiologic, and therapeutic data during hospitalization and prognosis were analyzed. Propensity-score matching (PSM) was performed to evaluate the risk of in-hospital adverse events, unfavorable outcomes at discharge when receiving post-stroke treatment and stroke recurrence. Results In all, 2,181 AIS patients were included, of whom 270 had UIAs (12.4%; 95%CI 11.0–13.8%). From the unmatched and matched cohort, the incidence of in-hospital adverse events and unfavorable outcomes at discharge in patients with UIAs were not significantly different; the risk of stroke recurrence was significantly higher in patients with UIAs than in those without (unmatched: aHR, 1.71 [1.08–2.70]; matched: aHR, 2.55 [1.16–5.58]). Multivariable Cox regression models showed that aneurysm size and the presence of homoregional infarction associated with higher risk of recurrence (unmatched: aHR, 1.31 [1.21–1.41] and aHR, 3.50 [1.52–8.10]; matched: aHR, 1.28 [1.18–1.40]; p < 0.001 and aHR, 3.71 [1.12–12.34]). Conclusion The UIAs may not increase the risk of in-hospital adverse events and unfavorable outcomes at discharge in receiving post-stroke treatment, but it may associated with a high risk of stroke recurrence.